Biographical puzzle, about the application of a biographical method in research on the history of the Rubinkowo estate in Toruń - Kmieć, Anna Natalia (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The article begins with an introduction in which I draw attention to the biographical method and the biographical interview technique, emphasizing the essence of their use in selected ethnographic research areas. I pay particular attention to the study of the history of ensembles, the whole. I am presenting the current state of my research on the history of the Rubinkowo estate in Toruń. Based on collected material, I present a biographical method using biographical interview as a way of looking at the history of the estate through the eyes of the individuals and through their experience. I emphasize the importance of applying this method in the knowledge and description of breakthroughs in the life and history of the place and the studied community. Biographical interwiev is a technique in which the interviewer conducts the researcher through his life, which also reflects – not always consciously and obviously – the history of the inhabited settlement. Summarizing, I demonstrate the specificity and legitimacy of the method I am using in the specific research on the reproduction of the history of the Rubinkowo estate in Toruń and postulate its application as a method leading in the bottom-up study of both the history and the ranges and directions of its formation.